Implementation’study of ISO 14001:2015 in the PT X Textile Industry, Karanganyar Regency, Central Java Using AHP Analysis - Putra, Yorra Anggara; Hasrianti, Hasrianti; Ridhowati, Sherly (Program Pascasarjana Universitas Sriwijaya, 2024)
PT X is one of the textile industries engaged in dyeing, printing and finishing and located in Karanganyar Regency, Central Java Province, production activities using various chemicals in PT X tend to reduce and even pollute the quality of the environment around the industrial area with the presence of B3 (Toxic and Hazardous Materials) waste generated. PT X has implemented ISO 9001: 2015 in relation to the quality management system, but in its application has not been efficient in understanding or managing the environmental problems caused so it is necessary to prepare SML (Environmental Management System) implementation of ISO 14001: 2015 in its production activities. The purpose of this study is to analyze the preparation of PT X and the perceptions of stakeholders in the implementation of ISO 14001: 2015 and strategies in its implementation. The research method was conducted with a documentation study, filling out the SML ISO 14001: 2015 checklist, an interview process with 5 stakeholders followed by recommendations for the implementation of environmental sustainability and data analysis using AHP through Expert Choice 11 application to determine the environmental sustainability strategy of SML ISO 14001: 2015. The GAP analysis checklist in PT X shows the SML ISO 14001: 2015 achievement value of 870 points of the total value 990 points so a percentage of 88.62% is obtained with the values of each clause reaching the highest Improvement 95.56%, followed by the Performance Evaluation clause 94.29% and the Operation clause 93.85%, Support 93.68% along with the Organizational Context clause 86.67%, Planning 83.33%, and the lowest is the value of the Leadership clause 72.49%. The results of the synthesis of ISO 14001: 2015 implementation strategies with the AHP method show the highest strategic value in the form of implementation of an Environmental Management System (EMS) with a ratio value of 0.458, followed by Human Resources planning of 0.291 and regulatory improvements of 0.131, while the lowest strategic value of 0.12 is the acquisition of new tools or technology (modernization).Keywords: Environmental Management System (EMS), ISO 14001:2015, GEMI checklist, AHP